5-BDBD ameliorates an OVA-induced allergic asthma by the reduction of Th2 cytokines production - Hu, Bing (Iran J Basic Med Sci, 2018)
OBJECTIVE(S): P2X4R is expressed in immunocyte and lung tissues. It has been a focus in inflammatory responses recently. This study investigated whether blockage of P2X4R attenuates allergic inflammation by modulating T cell response in ovalbumin-sensitized mice. MATERIALS AND METHODS: Ovalbumin was used to sensitize and challenge for a mouse model. Intranasal application of 5-BDBD, P2X4R antagonist, were performed 3 hr before each airway allergen challenge. The lung was evaluated for P2X4R by real-time PCR and immunofluorescence. Th1/Th2 cytokines in bronchoalveolar lavage fluid were measured by ELISA. T-bet, Gata-3, and p-p38 MAPK were measured by Western blot or real-time PCR. RESULTS: P2X4R was overexpressed in the lung after allergen challenge compared with the control group. Blockage of P2X4R decreased inflammation in the lung, IL-4 expression was reduced as well as IL-5; IFN-γ expression was elevated in BALF in ovalbumin-sensitized mice. Moreover, blockage of P2X4R inhibited ovalbumin-induced increased Gata-3 level and decreased T-bet level. CONCLUSION: These findings suggest that 5-BDBD ameliorates an ovalbumin-induced asthmatic attack by the downregulation of cytokines related to the Th2 cell.